Study of surgical fixation of extra-articular distal humerus fractures using extra-articular distal humerus locking plate - Manikandan Kumarasamy; K P Uma Anand; M Romans (Journal of Orthopaedic Diseases and Traumatology, 2022)
Background: The aim of this study was to evaluate the mechanical properties of distal humerus fracture fixation using extra-articular distal humerus locking plate osteosynthesis. There are numerous types of plates used in this region and one among them is the extra-articular distal humerus locking plate. This anatomically precontoured plate is specifically designed for the fixation of extra-articular distal humerus fractures. Usually, distal humeral extra-articular fractures are often associated with complications. This study reports satisfactory outcomes with the usage of extra-articular plate osteosynthesis for extra-articular humerus fracture management. It has now become a choice of management in our center for the management of extra-articular distal humerus fractures because of its advantages. We evaluated the clinical and functional outcomes of treating these fractures. Materials and Methods: We studied 20 patients who underwent fixation over 2 years. Mayo Elbow Performance Score was used to analyze functional outcomes. The time for union, range of motion at shoulder and elbow, and secondary procedures were recorded in follow-up. Shoulder and elbow function was assessed using the Mayo Elbow Performance Score. Results: During the study of 20 cases of distal humerus fractures treated by extra-articular distal humerus locking plate. Majority (40%) of the study participants were in the age group of 18–30 years. The mean age group is 39.8 years. Among 20 patients, thirteen were males and seven were female patients showing a male preponderance. About 14 and 6 patients with the right and left sides were involved, respectively. Eighty-five percent of the fractures united within 16 weeks, whereas for three patients (15%), fracture united at 18 weeks. The mean average time to union is 15.2 weeks. Eighteen (90%) patients had excellent elbow movement. Two (10%) patients had elbow stiffness. This was reduced to 32 weeks. All the patients were mobilized on day 2 after surgery. Eighteen patients (90%) had excellent results. Fair results were observed in two patients.